2014
DOI: 10.2147/dddt.s55458
|View full text |Cite
|
Sign up to set email alerts
|

Update on the clinical utility of once-daily tacrolimus in the management of transplantation

Abstract: Adherence to immunosuppression and minimizing variability in drug exposure are important considerations in preventing rejection and maximizing overall transplant outcomes. The availability of once-daily tacrolimus may confer potential benefit by simplifying immunosuppressive regimens, thereby improving medication adherence among transplant recipients. Pharmacokinetic studies in healthy normal volunteers and stable transplant recipients suggest that once-daily tacrolimus is bioequivalent to twice-daily tacrolim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Data on the clinical utility of once-daily tacrolimus were recently evaluated in a comprehensive review [68]. The authors of that review examined 17 efficacy and safety studies of once-daily tacrolimus (six in de novo kidney transplant recipients, five in stable kidney transplant recipients, one in both de novo and stable kidney transplant recipients, and five in liver transplant recipients).…”
Section: Efficacy and Safety Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Data on the clinical utility of once-daily tacrolimus were recently evaluated in a comprehensive review [68]. The authors of that review examined 17 efficacy and safety studies of once-daily tacrolimus (six in de novo kidney transplant recipients, five in stable kidney transplant recipients, one in both de novo and stable kidney transplant recipients, and five in liver transplant recipients).…”
Section: Efficacy and Safety Studiesmentioning
confidence: 99%
“…The vast majority of studies compared Advagraf Ò and Prograf Ò treatment. The authors of that review concluded that efficacy studies indicate that once-daily tacrolimus is non-inferior to twice-daily tacrolimus, with a concentration-dependent rejection risk [68]. The biopsy-proven acute rejection rates, though often higher with once-daily tacrolimus, were not statistically higher than those with twicedaily tacrolimus.…”
Section: Efficacy and Safety Studiesmentioning
confidence: 99%
See 3 more Smart Citations